Assessment of Distinct Electrophysiological Parameters in Rectal Biopsies for the Choice of the Best Diagnosis/Prognosis Biomarkers for Cystic Fibrosis - Silva, Iris A. L.; Duarte, Aires; Marson, Fernando A. L.; Centeio, Raquel; Doušová, Tereza; Kunzelmann, Karl; Amaral, Margarida D. (Frontiers in Physiology, 2020)
Most cases of Cystic Fibrosis (CF) are diagnosed early in life. However, people with atypical CF forms pose diagnosis dilemmas, requiring laboratory support for diagnosis confirmation/exclusion. Ex vivo analysis of fresh rectal biopsies by Ussing chamber has been the best discriminant biomarker for CF diagnosis/prognosis so far. Here we aimed to evaluate different electrophysiological parameters from Ussing chamber analysis of rectal biopsies from people with CF (PwCF) to establish the one with highest correlations with clinical features as the best CF diagnosis/prognosis biomarker. We analysed measurements of CFTR-mediated Cl- secretion in rectal biopsies from 149 individuals ( 610 biopsies), the largest cohort so far analysed by this approach. New parameters were analysed and compared with the previous biomarker, i.e., the IBMX (I)/Forskolin (F)/Carbachol (C)-stimulated short-circuit current (I’sc-I/F/C). Correlations with clinical features showed that the best parameter corresponded to voltage measurements of the I/F+(I/F/CCH) response (VI/F+I/F/C), with higher correlations vs I’sc-I/F/C for: sweat chloride (59% vs 52%), faecal elastase (69% vs 55%) and lung function, measured by FEV1 (27% vs 20%). Altogether data show that VI/F+I/F/C is the most sensitive, reproducible, and robust predictive biomarker for CF diagnosis/prognosis effectively discriminating classical, atypical CF and non-CF groups.